The Impact of Covid-19 on The Financial Performance of Property Companies Listed on The Indonesia Stock Exchange (IDX) - sihotang, benget rotua; Putra, Yananto Mihadi (Baca Dulu Publisher, 2024)
The Covid-19 pandemic is an event of increasing outbreaks of respiratory diseases in humans caused by the corona virus globally. COVID-19 first appeared in the city of Wuhan, China on December 31, 2019. The rapid spread of the Covid-19 outbreak has made the government make a number of anticipations to suppress its growth rate, including making policies, especially in the economic sector, namely implementing Social Restrictions (Physical Distancing). This research was conducted to determine whether there is a relationship between the dependent variable, namely the company's financial performance with the independent variable in the form of the impact of Covid-19 that occurs on property companies listed on the Indonesia StockExchange.This research is a type of quantitative research with the aim of examining the impact of Covid-19 on the financial performance of property companies listed on the Indonesia Stock Exchange (IDX). The research sample was selected using the purposive sampling method as many as 53 Property Companies Listed on the Indonesia Stock Exchange for the 2019-2020 period. Data collection is carried out by Documentation techniques. In this study, the data source used is secondary data. The analytical methods used in this study include: Using Descriptive Statistical Test and Wilcoxon Signed Rank Test.